AUTHOR STYLE IN THE DECORATIVE PAINTING OF CHINA AT THE MODERN STAGE (ON THE EXAMPLE OF DING SHAOGUAN’S CREATIVITY) - Діне, Ч. (Art and Design, 2024)
The purpose of the article is to understand the stylistic, compositional and coloristic solutions in the implementation of the author’s style of Ding Shaoguan in the decorative painting of China at the modern stage. The tasks of the class are the following: 1. to reveal the general stylistic elements of Ding Shaoguan’s creative output; 2. describe the main motifs of decorative paintings by the specified artist; 3. to investigate the stylistic, compositional and coloristic means of the author’s artistic expressiveness in the decorative painting of Ding Shaoguan. Methodology. Methods of formal-stylistic and compositional-coloristic analysis are used. The use of systematic analysis methods made it possible to identify the elements of the general style in which the decorative paintings of Ding Shaoguan are represented, as well as the original elements of the creative work of this Chinese master of decorative painting. The method of formal and stylistic analysis made it possible to analyze the stylistic features of Ding Shaoguang’s authorial style. Thanks to the method of compositional and color analysis, the article analyzes the main compositional and color techniques used by Ding Shaoguan in his original style of creating decorative paintings. The results. An analysis of the author’s style of the famous Chinese master of decorative painting Ding Shaoguan proves that with the emergence of certain socio-cultural conditions for the openness of modern China to the world, many domestic artists got the opportunity to receive art education abroad, to get acquainted with examples of Western art, while not forgetting their own ethnic roots. Among such artists was Ding Shaoguan, whose experience allowed him to integrate into his author’s style the stylistic findings of such a direction as art deco. Ding Shaoguan’s decorative paintings are distinguished by the presence of certain pictorial motifs, including: motifs with symbolic, not textual, wishes; floral motifs; ethno-historical motives. Graphically accurate delineation of the depicted women’s figures, typical for the artist; balanced symmetrical compositional solution; the smoothness of the lines of the general image, which sends the viewer to art deco, but with the author’s "remarks" are "name details" of the author’s style Ding Shaoguang. Signs of the author’s style of the artist in relation to the color solutions of his decorative paintings are a bright color scheme, or cold blue-blue-black-lilac colors or warm orange-red – yellow-brown colors with contrasting accents. The scientific novelty of the article lies in the fact that there are practically no art studies devoted to the Ding Shaogua author’s style. The practical significance of the obtained results lies in the possibility of their application for professional art education both in Ukraine and in China. The study opens the perspective of studying other images of everyday life in modern Chinese decorative painting.